Glycogen synthase kinase‐3 inhibitors suppress the AR‐V7‐mediated transcription and selectively inhibit cell growth in AR‐V7‐positive prostate cancer cells. Issue 9 (10th April 2017) - Nakata, Daisuke; Koyama, Ryokichi; Nakayama, Kazuhide; Kitazawa, Satoshi; Watanabe, Tatsuya; Hara, Takahito
Abstract : BACKGROUND: Recent evidence suggests that androgen receptor (AR) splice variants, including AR‐V7, play a pivotal role in resistance to androgen blockade in prostate cancer treatment. The development of new therapeutic agents that can suppress the transcriptional activities of AR splice variants has been anticipated as the next generation treatment of castration‐resistant prostate cancer. METHODS: High‐throughput screening of AR‐V7 signaling inhibitors was performed using an AR‐V7 reporter system. The effects of a glycogen synthase kinase‐3 (GSK3) inhibitor, LY‐2090314, on endogenous AR‐V7 signaling were evaluated in an AR‐V7‐positive cell line, JDCaP‐hr, by quantitative reverse transcription polymerase chain reaction. The relationship between AR‐V7 signaling and β‐catenin signaling was assessed using RNA interference. The effect of LY‐2090314 on cell growth in various prostate cancer cell lines was also evaluated. RESULTS: We identified GSK3 inhibitors as transcriptional suppressors of AR‐V7 using a high‐throughput screen with an AR‐V7 reporter system. LY‐2090314 suppressed the reporter activity and endogenous AR‐V7 activity in JDCaP‐hr cells. Because silencing of β‐catenin partly rescued the suppression, it was evident that the suppression was mediated, at least partially, via the activation of β‐catenin signaling. AR‐V7 signaling and β‐catenin signaling reciprocally regulate each other in JDCaP‐hr cells, and therefore, GSK3 inhibition can repress AR‐V7 transcriptional activity by accumulating intracellular β‐catenin. Notably, LY‐2090314 selectively inhibited the growth of AR‐V7‐positive prostate cancer cells in vitro. CONCLUSIONS: Our findings demonstrate the potential of GSK3 inhibitors in treating advanced prostate cancer driven by AR splice variants. In vivo evaluation of AR splice variant‐positive prostate cancer models will help illustrate the overall significance of GSK3 inhibitors in treating prostate cancer.